Regional Government Obligations in Fulfilling the Right to Clean Water - Nur Paikah; Paramita Yuliani; Maskawati (Journal of Indonesian Scholars for Social Research, 2025)
This study examines the regional government’s obligations in fulfilling the right to clean water to achieve public utility benefits, focusing on the Regional Water Utility Company (PDAM) in Bone Regency. The research adopts an empirical juridical method, combining field studies on the implementation of existing laws with data gathered through observation, interviews, and documentation. The results indicate that the fulfillment of the right to clean water by PDAM Bone Regency is not optimal. Challenges persist in three key aspects: quality, quantity, and continuity of water supply. The water quality often fails to meet standards, with issues such as turbidity reported by consumers. The quantity of water distributed remains insufficient to meet the needs of all citizens, particularly during extended dry seasons, and the continuity of water flow is inconsistent, disrupting daily activities. These issues hinder the realization of public welfare and equitable access to clean water, as mandated by Indonesia’s legal framework and human rights principles. This study highlights the need for improved management, infrastructure upgrades, and policy interventions to ensure the right to clean water is upheld for all citizens of Bone Regency.